Evaluating the Role of Hospital Leadership in Reducing Healthcare-Associated Infections - Alharbi, Nayef Humaid; Alshahrani, Saeed Ali; Alharbi, Khalid Hameed Rabah; Mufti, Hadi Ahmed; Aljohani, Abdullah Mahdaa; Almehmadi, Ziad Nasser; Alofi, Seham Fahad; Aloufi, Fahad Marzooq; Aljohani, Yousef Musallam; Al-Johani, Faisal Mohammed (Journal of Ecohumanism, 2024)
Healthcare-associated infections (HAIs) remain a major challenge in healthcare systems worldwide, contributing to increased patient morbidity, prolonged hospital stays, and substantial financial burdens. Hospital leadership plays a critical role in mitigating these infections by implementing evidence-based practices, fostering a culture of safety, and ensuring compliance with infection prevention protocols. This review examines the influence of leadership in reducing HAIs, focusing on strategic initiatives such as organizational commitment, multidisciplinary collaboration, and performance monitoring. By integrating robust leadership strategies and accountability frameworks, hospitals can significantly enhance patient safety and reduce the incidence of HAIs. The findings underscore the importance of leadership in driving sustainable change and highlight successful practices for future application.